2011
DOI: 10.1088/0953-2048/24/4/045010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for electromagnetic granularity in polycrystalline Sm1111 iron-pnictides with enhanced phase purity

Abstract: We prepared polycrystalline SmFeAsO 1-x F x (Sm1111) bulk samples by sintering and hot isostatic pressing (HIP) in order to study the effects of phase purity and relative density on the intergranular current density. Sintered and HIPped Sm1111 samples are denser with fewer impurity phases, such as SmOF and the grain boundary wetting phase, FeAs. We found quite complex magnetization behavior due to variations of both the inter and intragranular current densities. Removing porosity and reducing second phase cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
68
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 44 publications
(85 reference statements)
8
68
0
Order By: Relevance
“…Global supercurrent flow [36,84], and locally well-connected area [85,86] were confirmed to exist in this system.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Global supercurrent flow [36,84], and locally well-connected area [85,86] were confirmed to exist in this system.…”
mentioning
confidence: 57%
“…However, Yamamoto et al reported that even for the purest polycrystalline 1111 bulk samples made by the sintering and HIP process, their intergranular current densities are still small [84], providing further evidence that polycrystalline 1111 oxypnictides, like cuprates, are largely affected by weak-linked problems.…”
mentioning
confidence: 99%
“…Recently, the peak effect of J cm (B) in oxypnictide polycrystal [36] and single crystal [43] was verified to be caused by a first order phase transition from a ordered "elastically pinned" low-field vortex phase to a high-field disordered phase. weak links or local links due to Fe-As wetting phase on the grain boundary [19,25,27], and the number of strong links is very few. The well-connected structure of sample A increases the amount of weak links and local links, leading to the higher V sc and J cm (B) than sample B-F in lower fields.…”
Section: Density Effect On Critical Current Densitymentioning
confidence: 99%
“…However, the REFeAs(O, F) materials have short coherence length [15], low carrier density [16,17], significant evidence for granularity and low intergranular J c [18,19], which are similar to the case of cuprates. Many efforts were devoted to enhance the sample quality [19][20][21]. The SmFeAsO 1-x F x superconducting wires with high transport J c were successfully prepared by powder-in-tube (PIT) technique of both in-situ [22] and ex-situ [23] processes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the best transport critical current density, Jc, up to 10 5 -10 6 A/cm 2 in self field, has been obtained so far with the 122 family. 5,6 Recently, Jc values above the practical level (10 5 A/cm 2 at 10 T) have been Indeed, they suffer the loss of fluorine as a consequence of both the thermal treatment 9 and the strong interdiffusion with the metal sheaths. 10 Recently, a transport critical current density above 10 4 A/cm 2 at 4.2 K and in self-field has been achieved in 1111 tapes, but it is strongly suppressed by the field.…”
Section: Introductionmentioning
confidence: 99%